Near net shape machining by Micro-EDM and Micro-WEDM - Saleh, Tanveer; Bahar, Rubina (Springer, 2019)
Near net shape is a concept that is widely used in the recent years to address the issues of sustainability and resource optimization in the manufacturing sector. Near net shape (NNS) processes are the processes that require least or no post-processing to manufacture a product. Electro-discharge machining (EDM) is a non-conventional machining process that uses spark erosion principle for machining conductivematerial. If the tool in the EDMis a flexible metallic wire, then the process is termed as wire EDM. Further to this, when the discharge energy, tool and wire diameter, and the machined features are in micron domain, the machining technique is termed μEDM or μWEDM. In μEDM/μWEDM, the resultant structure does not require any post-processing to attain the final dimensional accuracy and surface finish; therefore, these processes can be considered as NNS processes. In this chapter, different applications of μEDM and μWEDM have been discussed as NNS process.